Skin infectome of patients with a tick bite history - Zhang, Jie; Zheng, Yuan-Chun; Chu, Yan-Li; Cui, Xiao-Ming; Wei, Ran; Bian, Cai; Liu, Hong-Bo; Yao, Nan-Nan; Jiang, Rui-Ruo; Huo, Qiu-Bo; Yuan, Ting-Ting; Li, Jie; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
With the advance of high-throughput sequencing, a variety of bacterial community and virome has been reported in tick, an obligate blood-feeding vector, which seems to pose a great threat to people. However, skin infectome from patients with a tick-bite is largely unknown, limiting our understanding on horizontal transmission of tick-borne pathogens via feeding on skins. Here, a total of 14 skin specimens collected from tick-bite patients with mild to severe symptoms were analyzed through meta-transcriptomic sequencings. Four bacteria genera were both detected in the skins and ticks, including Pseudomonas, Acinetobacter, Corynebacterium and Propionibacterium, and three tick-associated viruses, Jingmen tick virus (JMTV), Bole tick virus 4 (BLTV4) and Deer tick mononegavirales-like virus (DTMV) were identified in the skin samples. Except of known pathogens such as pathogenic rickettsia, Coxiella burnetii and JMTV, we suggest Roseomonas cervicalis and BLTV4 as potential new agents amplified in the skins and then disseminated into the blood. As early as 1 day after a tick-bite, these pathogens can transmit to skins and at most four ones can co-infect in skins. Skin should be an important barrier against tick-associated viruses or bacteria, deserving further investigation.